2019
DOI: 10.1002/aic.16624
|View full text |Cite
|
Sign up to set email alerts
|

Gas hold‐up and bubble behavior in an upflow packed bed column in the limit of low flow rate

Abstract: SignificanceGas-liquid up-flow in a packed bed is studied experimentally in the limit of zero flow rate.Two patterns of bubble behavior are detected based on the magnitude of the Bond number (Bo). The gas hold-up of the bed is found to be nonmonotonic with a maximum around Bo of unity. The bubble to particle diameter ratio is found to scale inversely with Bo. K E Y W O R D SBond number, bubble size, hold-up, packed bed, particle size

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…We refer to this flow regime as the "large bubble" (LB) regime. This regime is like that observed in normal gravity (at low Bond numbers) co-current up-flow at stationary or very low liquid flow rates and low gas flow rates 6 (except that the bubbles appearing in microgravity are larger). The pressure trace in Figure 3A shows a uniform pressure signal with several spikes correlating to the release of large bubbles trapped in the packing.…”
Section: Experiments and Test Conditionssupporting
confidence: 72%
“…We refer to this flow regime as the "large bubble" (LB) regime. This regime is like that observed in normal gravity (at low Bond numbers) co-current up-flow at stationary or very low liquid flow rates and low gas flow rates 6 (except that the bubbles appearing in microgravity are larger). The pressure trace in Figure 3A shows a uniform pressure signal with several spikes correlating to the release of large bubbles trapped in the packing.…”
Section: Experiments and Test Conditionssupporting
confidence: 72%
“…That is because for a gas bubble in a stationary packed bed, two main forces act: surface tension and buoyancy. Surface tension force tends to push the bubble downward, while buoyancy force tends to push the bubble upward 9 . The Bond number ( Bo ) is defined as the ratio of buoyancy force to surface tension force: Bo=ρnormallitalicgdnormalp2σ …”
Section: Resultsmentioning
confidence: 99%
“…Surface tension force tends to push the bubble downward, while buoyancy force tends to push the bubble upward. 9 The Bond number (Bo) is defined as the ratio of buoyancy force to surface tension force:…”
Section: Gas Holdupmentioning
confidence: 99%
See 1 more Smart Citation
“…This flow regime can also be observed in normal gravity gas–liquid two‐phase up‐flows in packed‐beds but requires that the Bond number be much smaller than unity. For example, normal gravity experiments 21 have shown that the ratio of the bubble to packing particle diameter is inversely proportional to the Bond number (Bo=ρLgdp2σ). In microgravity, the Bond number approaches zero indicating that the bubble diameter can be very large compared to the packing size.…”
Section: Summary and Discussionmentioning
confidence: 99%